Online Consumer Fraud Victimization and Reporting: A Quantitative Study of the Predictors and Motives - Fonseca, Catarina (Victims & offenders, 2022)
Online consumer fraud is one of the most fast-growing crimes. It corresponds to situations where, for instance, the products that are bought, but are not delivered. The present study (N = 1710) aimed at exploring, on the one hand, the predictors of online fraud victimization and, on the other hand, to examine the reporting to the police. Even though 223 were victims of online consumer fraud, only 20 reported to the police. Moreover, while individual variables were not predictors of victimization, online routines were relevant to its explanation. Finally, monetary loss was the most important predictor of reporting to the police.